Projections of future mortality risk in older adults from high-tide flooding in coastal areas of the USA: An economic modelling study - Sheahan, Megan B.; Hauer, Mathew; Mueller, Valerie; Sheriff, Glenn; Fant, Charles; Holland, Isabel; Sarofim, Marcus C.; Hartin, Corinne; Neumann, James E. (Elsevier, 2025)
Background Studies have documented the effect of increased nuisance high-tide flooding on traffic disruption and delays as well as infrastructure maintenance and repair costs. Recent research suggests that high-tide flooding is also associated with more extreme outcomes, including increased mortality risk among adults aged 65 years and older. The aim of this study was to leverage these new findings to project future premature deaths and associated economic costs among older adults in coastal areas of the USA throughout the 21st century under various climate change scenarios.